Fauna and flora, earth and sky : brushes with nature's wisdom - Dittmar, Trudy, 1944- (Sightline books., 2003)
"[Fauna and Flora, Earth and Sky] is, in fact, the most intelligent, thoughtful, original, challenging, and highly entertaining work of nature writing since Barry Lopez's Artic Dreams. ... It is her broad scope of contemplation, combined with her fiercely beautiful and detailed renderings of passion, natural and human, that give Trudy Dittmar's first but fully mature book its remarkable originality and considerable power."--Robert Finch, Los Angeles Times Book Review